ON HAMLET’S CRYPT: EFFI BRIEST, ASTA NIELSEN, AND BRITNEY SPEARS - Kolarov, Viola (Imaginations: Journal of Cross-Cultural Image Studies, 2011)
This contribution looks at the way instinct is transmitted and represented as ghost appearance. The essay elaborates two basic theses: first, that instinct is not defined by creaturely heritage, since it is not a testable structure in itself, nor subject to mourning and developmental processes; and second, that works of fine literature and pop oeuvres alike may serve as carriers of a ghost transmission charged with instinctive heritage. The study represents a model for reading ghostly genealogies that complement the familiar and familial reproductive ones as it draws on traditions such as the adultery novel, continental philosophy, psychoanalysis, and Disney. Currently based in Berlin, Viola Kolarov has taught in the German Departments of the Johns Hopkins University and New York University. She has published on Shakespeare, contemporary art, film, and pop culture. Her forthcoming book, “Shakespeare and the Autobiography of the Machine Age,” rethinks Goethe, the German translation/transmission of Shakespeare, and the German literary tradition in the contexts of media technology. Originally from Berlin, Susanne Lanckowsky entered the Academy of Fine Arts Karlsruhe, class of Franz Ackermann, in 2007. Since 2009 she has shown solo and in group on numerous occasions and studied abroad with prestigious scholarship support for one semester at the Faculdade de Belas Artes Universidade do Porto, Portugal, and for another semester at the Escuela Nacional de Pintura, Escultura y Grabado La Esmeralda in Mexico.